Diseño del direccionamiento y plan estratégico de la microempresa Chepas Franciscanas S.A.S en Bolivar-Colombia (2021)
This paper presents a proposal for the direction and strategic plan to promote the growth of the microenterprise Chepas Franciscanas S.A.S, located in Carmen de Bolívar, this was carried out from a descriptive research, using a qualitative approach combining induction and analysis. To obtain the required information, instruments such as non-participant direct observation, workshops on internal and external factors, values and principles, virtual interviews, tools such as SWOT analysis, POAM and PCI, Michael Porter's 5 forces, strategic map and the tool were used. Balanced Scorecard. For the design of the proposal and the fulfillment of the objectives, an exhaustive investigation was carried out in which the theoretical references on the subject under study were analyzed. In addition, in search of a direction and strategic plan that adjusts to the needs of the microenterprise under study, an analysis of three models was carried out (Model of Kaplan and Norton (2015), Model Serna, H. (2014) and Model by David Fred R. (2003)), allowing the definition of the model to be implemented in Chepas Franciscanas S.A.S Coming to the conclusion that the most appropriate model to boost growth is the model proposed by Serna, it should be noted that this model was taken as a reference but was not fully implemented.v